2019
DOI: 10.1111/apel.12254
|View full text |Cite
|
Sign up to set email alerts
|

Monetary policy responses of Asian countries to spillovers from US monetary policy

Abstract: Regional integration in Asia has been considerably enhanced over the past 20 years or so. Whether integration helps Asian countries reduce their vulnerability to external shocks or is a channel for spreading external shocks remains an open question. This paper assesses the spillovers from US monetary policy shocks to Asian countries while taking into account country‐specific characteristics in explaining differences in timing and magnitude of responses across Asian countries. The results indicate that policy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 46 publications
3
20
0
Order By: Relevance
“…We observed that interest rate in Nigeria is likely to be driven by own innovations and shocks within, given our findings of no evidence of significant spillover effects of monetary policy in US to interest rate. This is in line with some of the findings from the previous studies (see Pham and Phuc, 2019),but it is mainly with respect to the mean equation of the estimated model as far as this present study is concerned. However, our empirical finding from the variance equation suggests that there is a volatility spillover effect of monetary policy in US to interest rates in Nigeria at least in the short run situation.…”
Section: Conclusion and Policy Recommendationssupporting
confidence: 94%
See 2 more Smart Citations
“…We observed that interest rate in Nigeria is likely to be driven by own innovations and shocks within, given our findings of no evidence of significant spillover effects of monetary policy in US to interest rate. This is in line with some of the findings from the previous studies (see Pham and Phuc, 2019),but it is mainly with respect to the mean equation of the estimated model as far as this present study is concerned. However, our empirical finding from the variance equation suggests that there is a volatility spillover effect of monetary policy in US to interest rates in Nigeria at least in the short run situation.…”
Section: Conclusion and Policy Recommendationssupporting
confidence: 94%
“…Table 4 show that there no evidence of significant spillovers effect of CMP on interest rate in Nigeria. This which finds support in Pham and Phuc (2019) is an indication that interest rate in Nigeria is driven mainly by own innovation as captured by the coefficient on the lagged term (ψ 11 ) of interest rate. We however, observed evidence of positive and significant shock spillover effects of CMP on interest rate (φ 12 ).…”
Section: Empirical Analysesmentioning
confidence: 85%
See 1 more Smart Citation
“…The responses of central banks in these regions show that central banks are gradually losing their independence to decide their monetary policy stances. Pham and Nguyen (2019) evaluate the spillover effect of UMP from the US on the monetary policies in Asian countries by a Bayesian vector autoregressive model. To address such an issue, this research considers how policy rates in Asian countries respond to the shock to the Fed policy rate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, rigorous empirical analysis is essential to draw a firm conclusion in this regard. The spillover of foreign interest rates to advanced and emerging economies has been well-researched, most recently by Iacoviello and Navarro (2019) and Pham and Nguyen (2019). Iacoviello and Navarro (2019) find that the U.S. interest rates are transmitted through the channels of the exchange rate, trade and finance, but that these transmissions are largely heterogeneous between advanced and emerging economies.…”
Section: Impact Of Foreign Interest Ratementioning
confidence: 99%